2017
DOI: 10.47263/jasem.1(1)06
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Empowerment and Job Involvement

Abstract: Job involvement is the psychological identification with one‟s job. Studies show that those with high job involvement are inversely related to absenteeism, positively related to organizational citizenship behavior and in-role performance, organizational identification and employee commitment. Meanwhile psychological empowerment is a motivational construct that comprises individual cognitions and perceptions that constitute feelings of behavioral and psychological investment in a work. Empirical research on emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…First, we found that psychological empowerment promotes job involvement. Previous studies have shown that psychological empowerment is an important incentive resource and can enhance employees' job involvement (Ugwu et al, 2014 ; Razak et al, 2017 ), our study confirms this relationship. The nature of kindergarten teachers' work is different from that of primary and secondary school teachers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, we found that psychological empowerment promotes job involvement. Previous studies have shown that psychological empowerment is an important incentive resource and can enhance employees' job involvement (Ugwu et al, 2014 ; Razak et al, 2017 ), our study confirms this relationship. The nature of kindergarten teachers' work is different from that of primary and secondary school teachers.…”
Section: Discussionsupporting
confidence: 89%
“…Demir ( 2020 ) found that, when teacher self-efficacy was higher, so was their job involvement. Razak et al's ( 2017 ) survey of 151 bank managers confirmed a positive correlation between psychological empowerment and job involvement. In China, Jiang and Han ( 2010 ) and Chen ( 2013 ) also found a positive relationship between psychological empowerment and job involvement.…”
Section: Introductionmentioning
confidence: 94%
“…Razak, Zakaria, and Mat (2017) stressed that employee attitudes are crucial because they affect their job behaviors. Almost four decades ago, Moch (1980) emphasized the lack of studies to examine the effect of job characteristics on intrinsic motivation and job involvement.…”
Section: Introductionmentioning
confidence: 99%